Leaf diagnosis and soybean yield after residues application in an oxisol under no-till - Cardoso dos Santos, Susiane Moura; Antonagelo, Joao Arthur; Fernandes Deus, Angelica Cristina [UNESP]; Bull, Leonardo Theodoro [UNESP] (Univ Estadual Mato Grosso Sul, 2018)
The surface application of residues and the non-soil revolving due to no-till (NT) favor the chemical, physical and biological soil attributes and affect the nutrients dynamics along its profile. In addition of being amendments of soil acidity, some residues are excellent sources of bioavailable nutrients, such as nitrogen, phosphorus and calcium as macronutrients, and zinc and manganese as micronutrients. In this context, we aimed to evaluate the nutritional status and grain yield of soybean (Glycine max) cultivated under NT in an Oxisol subjected to surface application of urban and industrial residues. The experimental design was the randomized block with four replications (n=4). The treatments consisted of four residues: sewage sludge centrifuged and treated with virgin lime (LC), biodigestor sewage sludge (LB), steel slag (E) and lime sludge (Lcal), applied at four doses: 0 (control), 2, 4 and 8 Mg ha(-1). There was an increase in the N, P and Ca contents in the soybean leaves. However, the Mn and Zn contents decreased as the doses of residues increased, except for the dose of 8 Mg ha(-1). The increased doses of residues applied increased the grain yield in the soybean crop.
Keywords: sewage sludge; lime sludge; steel slag; Glycine max